Rasch modeling: Developing a critical thinking ability test for students on climate change material - Irwan Muhammad Ridwan; Ida Kaniawati; Andi Suhandi; Taufik Ramlan Ramalis; Ifa Rifatul Mahmudah; Berry Kurnia Vilmala (Momentum: Physics Education Journal, 2023)
The goal of this study was to examine critical thinking skills on the topic of climate change. This study is quantitative in nature. The information was gathered by creating a 30-question test to assess the ability to think critically about climate change. Respondents were 52 physics education students from one of Tasikmalaya's campuses. Winstep software version 4.00 was utilized for data analysis. Rasch modeling was employed in this investigation. The results of the Rasch modeling study show a value of 0.38 for person reliability and 0.91 for item reliability, indicating that the instrument items manufactured are dependable. The raw variance value of 23.4% suggests that the standards for dichotomous data construct validity are met. The separation value of 3.15 supports this. It suggests that this item has a good answer distribution and can assess critical thinking skills on the topic of climate change. As a result, it can be used for study.